The Development of Strategic Bank Lending Industries in the Context of Globalization - Kramarenko, Oksana Markovna (Economy of Regions, 2015)
It is shown that, in the context of globalization, improved credit support for strategic sectors of the economy (for example, shipbuilding) can be achieved through the creation of a banking consortium based around leasing. A dialectical method of resolution of system tasks is selected as the methodological approach. Methods used include: comparative cost analysis of the strategic lending industry supporting the formation and development of a banking consortium; integrated method at the condition modeling of making and implementation of a lease agreement, which allowed to accommodate the interests for both parties of such agreement; optimization method to select the conditions of a lease agreement; classification and analytical method to clarify the classification of lease. The study proved and developed a plan of creation a banking consortium, including options of interaction of such consortium with potential customers based on a lease agreement. The process of functioning of the lease agreement in order to optimize it for both a bank consortium-lessor and a lessee is modeled. The significant advantages of leasing compared to the traditional lending for both parties of leasing, especially when ensuring long-term projects are summarized. The results of the research can be applied in the strategic lending industries development and can reduce the level of banking risks. Applying the results of the research in the social aspect can maintain and increase the number of jobs including the banking sector. The value of the work leis in the fact that the author has developed a new approach to achive the credit support for strategic sectors of the economy through the creation of the banking consortium based around leasing, which allows to protect the interests of both parties.